2020
DOI: 10.1089/fpd.2019.2709
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Toxigenic Heterogeneity of Bacillus cereus sensu lato Isolated from Ready-to-Eat Foods and Powdered Milk in Day Care Centers in Colombia

Abstract: Bacillus cereus sensu lato (s.l.) is a group of bacteria commonly found in diverse environments, including foods, with potential to cause emesis and diarrhea. In Colombia, it is one of the main foodborne pathogens. The aim of this study was to determine the genomic and toxigenic heterogeneity of B. cereus s.l. isolated from ready-to-eat foods and powdered milk collected in day care centers of Medellin, Colombia. Of 112 B. cereus s.l. isolates obtained, 94% were b-hemolytic. Toxigenic heterogeneity was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
2
11
2
Order By: Relevance
“…Worldwide, incidences of B. cereus s.l. are variable; the values reported are either higher or lower than the ones obtained in this study; however, as long as the food raw-materials and flours are handcrafted and slightly processed, they are susceptible to contamination by B. cereus spores and vegetative cells, constituting great risk for human health [12,13]. Studies performed in countries such as Korea found B. cereus in 40% of raw rice samples [23]; in Iran, 42% of infant formula analyzed carried B. cereus [24] and in New Zealand, B. cereus incidences in dehydrated potato ranged from 10% to 40% [25].…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Worldwide, incidences of B. cereus s.l. are variable; the values reported are either higher or lower than the ones obtained in this study; however, as long as the food raw-materials and flours are handcrafted and slightly processed, they are susceptible to contamination by B. cereus spores and vegetative cells, constituting great risk for human health [12,13]. Studies performed in countries such as Korea found B. cereus in 40% of raw rice samples [23]; in Iran, 42% of infant formula analyzed carried B. cereus [24] and in New Zealand, B. cereus incidences in dehydrated potato ranged from 10% to 40% [25].…”
Section: Discussioncontrasting
confidence: 64%
“…Various works around the world have reported a high genomic diversity on B. cereus s.l. from foods such as ready-to-eat [11,12] and powdered products [13], milk [6,14] and others [15], as well as a broad distribution of toxin genes in B. cereus s.l. isolated from foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of the gene is now routinely assessed in combination with other diarrheal toxins-encoded genes such as ces, nhe and hbl to determine the potential pathogenicity of a strain. Data show that cwpFM is widely distributed (detection rate of 68-98%) in B. cereus isolated from diverse food matrices [53][54][55][56][57]. cwpFM is also detected in strains associated with food-borne illnesses [33,58] and is even present in emetic strains [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be pointed out that in several studies the ces gene cluster (encoding cereulide synthetase) is not investigated or not mentioned [119][120][121], and that several studies do not distinguish between emetic and enteropathogenic B. cereus at all [122,123]. If the emetic toxin genes are investigated, their occurrence is rather rare compared to the enterotoxin genes ( Table 2 and [124][125][126][127][128][129]). Other studies challenge the tight association of emetic B. cereus with starchy foodstuffs and suggest a rather heterogeneous distribution.…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 99%